2011
DOI: 10.1002/nag.1053
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of rock aggregate breakage properties using realistic texture‐based modelling

Abstract: SUMMARYRealistic texture-based modelling methods, that is microstructural modelling and micromechanical modelling, are developed to simulate the rock aggregate breakage properties on the basis of the rock actual microstructure obtained using microscopic observations and image analysis. The breakage properties of three types of rocks, that is Avja, LEP and Vandle taken from three quarries in Sweden, in single aggregate breakage tests and in inter-aggregate breakage tests are then modelled using the proposed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The application of brittleness evaluation methods based on stress-strain curves are generally limited to laboratory tests on cores drilled from certain glutenite layers, making it difficult to obtain continuous longitudinal mechanical properties and stress-strain responses of glutenite reservoirs under different in situ stresses. Therefore, to make brittleness models more applicable to fracturing operations and to obtain a continuous longitudinal brittleness index of glutenite throughout the well, it is necessary to integrate geomechanical and petrophysical approaches [51][52][53][54]. There is an intrinsic relationship between geophysical logging data and the physical and mechanical parameters of the reservoir rock mass [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of brittleness evaluation methods based on stress-strain curves are generally limited to laboratory tests on cores drilled from certain glutenite layers, making it difficult to obtain continuous longitudinal mechanical properties and stress-strain responses of glutenite reservoirs under different in situ stresses. Therefore, to make brittleness models more applicable to fracturing operations and to obtain a continuous longitudinal brittleness index of glutenite throughout the well, it is necessary to integrate geomechanical and petrophysical approaches [51][52][53][54]. There is an intrinsic relationship between geophysical logging data and the physical and mechanical parameters of the reservoir rock mass [2].…”
Section: Discussionmentioning
confidence: 99%
“…The peak strength and elastic modulus of glutenite specimen remain almost invariant, while the residual strength decreases with an increase in gravel size, which results in an increase in glutenite brittleness. Fracture deflection by gravel can lower the fracture-tip stress intensity and enhance the fracture growth resistance, and the fracture may undergo a "shielding" effect [52][53][54]. When a fracture approaches large-sized gravel, it must accumulate more energy to overcome the resistance.…”
Section: Bimentioning
confidence: 99%
“…In addition, Ingraffea, Whittaker et al, and Al-Shayea et al indicated that model-II fracture toughness K IIc is usually larger than mode-I fracture toughness K Ic [32][33][34]. According to Brazilian disc tests for limestone rock, the ratio of K IIc /K Ic is 1.72 [35], while it is 1.64 obtained from numerical modelling of the notched Brazilian disc test for granite materials [36]. Accordingly, the mode-II fracture toughness is assumed to be 1.7 times larger than the mode-I fracture toughness.…”
Section: Modelling Rock Fracture During the Uniaxial Compressivementioning
confidence: 99%
“…Further loading causes the three pieces sliding along the formed two shear cracks. Microstructure or statistical methods, such as those proposed by Liu et al (2012), may be introduced based on the actual texture of rock to obtain reasonable failure pattern as observed in experiments. Figure 4 visually illustrates the modelled rock disc splitting failure process in terms of the distributions of the minor principal stress (the compressive stress) and the initiated cracks during the BTS test while the corresponding force and displacement curve is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%